2013
DOI: 10.1007/s11524-013-9786-y
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disadvantage, High Alcohol Content Beverage Consumption, Drinking Norms, and Drinking Consequences: A Mediation Analysis

Abstract: Alcohol use can cause significant harm. We examined the relationships between neighborhood disadvantage, consumption of high-alcohol-content beverages (HACB), drinking norms, and self-reported drinking consequences using data from the 2000 and 2005 National Alcohol Surveys (N09,971 current drinkers) and the 2000 Decennial Census. We hypothesized that (1) individuals living in disadvantaged neighborhoods would report more negative drinking consequences than individuals living in more affluent neighborhoods, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 67 publications
(92 reference statements)
1
25
0
Order By: Relevance
“…Beer is more affordable than most wine and liquor, so our results may simply reflect financial preferences. Jones-Webb and Kariker-Jaffee (2013) examined the association between neighborhood disadvantage and high alcohol content consumption and found that disadvantage was associated with the consumption of malt liquor and fortified wine but not high spirit volumes. Although additional research is necessary to better understand how neighborhood SES influences specific types of alcohol use, our results are in accordance with the limited evidence that the neighborhood context is not equally associated with all types of alcohol use (Jones-Webb & Karriker-Jaffe, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Beer is more affordable than most wine and liquor, so our results may simply reflect financial preferences. Jones-Webb and Kariker-Jaffee (2013) examined the association between neighborhood disadvantage and high alcohol content consumption and found that disadvantage was associated with the consumption of malt liquor and fortified wine but not high spirit volumes. Although additional research is necessary to better understand how neighborhood SES influences specific types of alcohol use, our results are in accordance with the limited evidence that the neighborhood context is not equally associated with all types of alcohol use (Jones-Webb & Karriker-Jaffe, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One of the strengths of our study was the focus on multiple patterns of alcohol use and types of alcohol consumed. Only two studies of which we are aware examined neighborhood effects on beverage-specific alcohol use (Picone et al, 2010, Jones-Webb and Karriker-Jaffe 2013). Developing a better understanding of how neighborhood context influences beverage-specific alcohol use has several important public health implications.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review (Jackson et al, 2014), most studies did not find significant associations between disadvantage and alcohol use that may be partly attributable to lack of consideration of effect modifiers and the use of different definitions of neighborhood disadvantage. Many studies lack generalizability by focusing on samples with limited racial/ethnic diversity, or high-risk youth (Buu et al, 2009; Fite et al, 2009; Fuller et al, 2005; Jones-Webb and Karriker-Jaffe, 2013), and are older studies (Crum et al, 1996) that may not accurately reflect current neighborhood socioeconomic conditions or current ATOD use patterns.…”
Section: Introductionmentioning
confidence: 99%